Preparation of Fe(II)/MOF-5 Catalyst for Highly Selective Catalytic Hydroxylation of Phenol by Equivalent Loading at Room Temperature - Bai-Lin Xiang; Lin Fu; Yongfei Li; Yuejin Liu (Journal of Chemistry)
The metal-organic framework MOF-5 was synthesized by self-assembling of Zn(NO3)2·7H2O and H2BDC using DMF as solvent by the direct precipitation method and loaded with Fe2+ by the equivalent loading method at room temperature to prepare Fe(II)/MOF-5 catalyst and the microstructure, phases, and pore size of which was characterized by IR, XRD, SEM, TEM, and BET. It was found that Fe(II)/MOF-5 had high specific surface and porosity like MOF-5 and uniform pore distribution, and the pore size is 1.2 nm. In order to study the catalytic activity and reaction conditions of Fe(II)/MOF-5, it was used to catalyze the hydroxylation reaction of phenol with hydrogen peroxide. The results showed that the dihydroxybenzene yield of 53.2% and the catechol selectivity of 98.6% were obtained at the Fe2+ content of 3 wt.%, the mass ratio of Fe(II)/MOF-5 to phenol of 0.053, the reaction temperature of 80°C, and the reaction time of 2 h.